Evaluation Expression of miR-146a and miR-155 in Non-Small-Cell Lung Cancer Patients - Dezfuli, Neda K.; Alipoor, Shamila D.; Dalil Roofchayee, Neda; Seyfi, Sharareh; Salimi, Babak; Adcock, Ian M.; Mortaz, Esmaeil (Frontiers in Oncology, 2021)
Background: Non‑small cell lung cancer (NSCLC) is the major type of lung cancer. MicroRNAs (miRNAs) are currently considered as novel markers and targets in cancer therapy and can act as both tumor suppressors and oncogenes. The immunologic effects of this miRNAs still is interesting studies and in progressing. The aim of this study was to investigate the expression of miR146a and miR155 in linked to blood immune cells phenotypes and serum cytokines in NSCLC patients. Methods: Thirty three NSCLC patients and thirty healthy subjects were enrolled in this study. Besides, the allele frequencies of possible polymorphisms of genomic DNA of blood cells was studied using polymerase chain reaction–restriction fragment length polymorphism (PCR-RFLP) method. Quantitative real-time PCR (qRT-PCR) was used for the measurement of the expression level of miR-146a and miR-155 in peripheral blood mononuclear cells (PBMCs). Serum cytokines (IL-1, IL-6, TNF-α, TGF-β, IL-4, IFN-) levels was determined by ELISA methods. In immunophenotyping analysis the frequency of circulating CTLA4+CD3+ and CD4+CD25+FOXP3+ (T regulatory cells/Treg) and CTLA4 and FOXP3 expression were measurement by flow cytometer Results: miR-146a was significantly downregulated in PBMC of NSCLC patients (P≤0.001). Moreover, IL-6 and TGF-β levels were elevated in NSCLC patients (P≤0.001, P≤0.018 respectively). CTLA4+CD3+ and T reg cells frequency were higher in patients (P≤ 0.0001, P≤ 0.0001 respectively). CTLA4 and FOXP3 expression were higher in NSCLC patients (p≤ 0.0001, P≤0.0001 respectively). No significant difference was found in relative expression of miR-146a and miR-155, cytokines levels and immune cells in genotypes of miR-146a and miR-155 (GG/GC/CC, TT/AT/AA) in patients. . A positive correlation between miR-155 expression and IL-1β (r = 0.58, p≤0.009) in TT genotype , a positive correlation between miR-155 expression andCD3+CTLA4+ cells frequency (r = 0.75, P≤0.01) in AT genotype was observed. Conclusions: The current data suggests that the miR-146a expression and TGF-β levels could be give information regarding to outcome of NSCLC and further study is needed to be done.